Effect of exercise-based cardiac rehabilitation on dyspnoea in heart failure: A systematic review of assessment tools, outcomes, and FITT parameters - García-Conejo, Celia; Roldán-Jiménez, Cristina; Cuesta-Vargas, Antonio (ELSEVIER, 2025)
Exercise-based cardiac rehabilitation (EBCR) programmes are strongly recommended to enhance exercise capacity and quality of life in heart failure (HF). However, their effects on dyspnoea have not been systematically reviewed, possibly due to the knowledge gap in the assessment of dyspnoea. The aim of this study was to recognise the dyspnoea tool used in HF for the EBCR trial, assess the effects of EBCR on dyspnoea and identify which patient characteristics and FITT parameters (Frequency, Intensity, Time and Type) are associated with better outcomes. A review and meta-analysis of randomised controlled trials following the PRISMA guideline were performed, including fifteen studies (n = 766 participants). Up to 8 dyspnoea measurement instruments were identified in the studies. EBCR showed a moderate effect size on dyspnoea (d = 0.69, 95% CI 0.54–0.84). Larger effects were seen in patients < 65 years (d = 0.77, 95% CI 0.54–0.99) and in non-hospitalised patients (d = 0.735, 95% CI 0.550–0.921). Greater effects were observed for low-intensity (d = 0.79, 95% CI 0.44–1.15) and multimodal programmes (d = 1.12, 95% CI 0.47–1.77). Programmes with three sessions per week and ≥12 weeks were the most common. Findings were limited due to the varying dyspnoea scales, highlighting the need for standardised assessment in HF.
Keywords: Insuficiencia cardíaca; Fisioterapia; Pacientes -- Rehabilitación; Ejercicio físico -- Uso terapéutico; Heart failure; Dyspnoea; Cardiac rehabilitation; Exercise therapy